China-Canada Economic Relations in the Early 21st Century - Rahman, Md. Sayedur; Sujan, Saymon Ahamed (Sahayaatra सहयात्रा, 2024)
In Canada's corporate and political communities, it is now commonly acknowledged that China is becoming a global economic superpower. For instance, it is now accepted knowledge that all companies, and even all government agencies, must create a "China Strategy," whether or not they conduct any business with China directly. Since the conclusion of the Cold War, China has assumed a larger role in world geopolitics and gained the attention of the most influential political figures. Canada is a prime example of a selective or specialized power today and looks to have established its steady place in international affairs. In order to assess the position of the modern People's Republic of China (PRC) in Canadian foreign policy, this paper explores Canada-China relations from the most current angle. This study examines several facets of bilateral ties, including human rights and democracy, economics and commerce, the ability of Chinese Canadians to advocate and their impact on Ottawa's PRC policies. An overview of the development of ties between Canada and China is also included in the article.